2016
DOI: 10.1161/circulationaha.115.018580
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness and Safety of Pravastatin in Patients With Coronary Heart Disease

Abstract: Many trials have shown that inhibitors of 3-hydroxy-3-methylglutaryl-coenzyme A reductase (or statins) reduce the risk of death and major cardiovascular events after acute myocardial infarction and unstable angina pectoris. [1][2][3][4] One of these, the Long-term Intervention with Pravastatin in Ischemic Disease (LIPID) trial, showed that 6 years of pravastatin treatment resulted in better survival. 4 The longer-term effects of statins on cause-specific mortality and net clinical benefit are still debated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Alternatively, hydrophilic statins, such as pravastatin, may not be as effective as lipophilic agents, such as simvastatin; some studies have suggested clearer benefits for simvastatin in lung cancer, 21 with a lack of benefit for pravastatin in cancer prevention or cancer death observed in a trial of patients with coronary heart disease. 29 However, there is insufficient evidence to reliably conclude whether any one type of statin is better than another, and biologic plausibility for a difference is lacking. 22 Of interest, more recent evidence in glioma cells has suggested that statins may fail to work in certain cancer cells because of a phosphatidylinositol 3-kinase–mediated pathway connected to LDL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, hydrophilic statins, such as pravastatin, may not be as effective as lipophilic agents, such as simvastatin; some studies have suggested clearer benefits for simvastatin in lung cancer, 21 with a lack of benefit for pravastatin in cancer prevention or cancer death observed in a trial of patients with coronary heart disease. 29 However, there is insufficient evidence to reliably conclude whether any one type of statin is better than another, and biologic plausibility for a difference is lacking. 22 Of interest, more recent evidence in glioma cells has suggested that statins may fail to work in certain cancer cells because of a phosphatidylinositol 3-kinase–mediated pathway connected to LDL receptors.…”
Section: Discussionmentioning
confidence: 99%
“…From this time, surviving patients were followed up centrally by the National Health and Medical Research Council Clinical Trials Centre until the end of 2007 7. Information on cause-specific mortality and cancer incidence was also obtained through data linkage with national death registries and state-based cancer registries in Australia and New Zealand 7. The outcome measures were CV death and all-cause mortality obtained for all patients after 48 months for further follow-up over a median of 12.1 (IQR 8.6–12.5) years.…”
Section: Methodsmentioning
confidence: 99%
“…Over the total period, the reductions in all‐cause mortality remained statistically significant (RR, 0.91; 95% CI, 0.85‐0.97; P = .003). There were no significant differences in cancer mortality (RR, 1.01; 95% CI, 0.85‐1.15; P = .87), nor in cancer incidence (RR, 0.99; 95% CI, 0.91‐1.08; P = .83) . The Scandinavian Simvastatin Survival Study Group (4S) trial was also a double‐blind RCT of simvastatin or placebo in 4444 patients with coronary heart disease with a total median follow‐up of 5.4 years.…”
Section: Resultsmentioning
confidence: 99%